2017
DOI: 10.3389/fpls.2017.00915
|View full text |Cite
|
Sign up to set email alerts
|

LeafletAnalyzer, an Automated Software for Quantifying, Comparing and Classifying Blade and Serration Features of Compound Leaves during Development, and among Induced Mutants and Natural Variants in the Legume Medicago truncatula

Abstract: Diverse leaf forms ranging from simple to compound leaves are found in plants. It is known that the final leaf size and shape vary greatly in response to developmental and environmental changes. However, changes in leaf size and shape have been quantitatively characterized only in a limited number of species. Here, we report development of LeafletAnalyzer, an automated image analysis and classification software to analyze and classify blade and serration characteristics of trifoliate leaves in Medicago truncat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 31 publications
1
10
0
Order By: Relevance
“…The potential use of phenomics in fruit shape description in tomato and eggplant has also been demonstrated (Brewer et al 2006;Plazas et al 2014), and its subsequent use in plant breeding (Kaushik et al 2016). In accordance with our results, quantification of leaf shape in barley (Chitwood et al 2013(Chitwood et al , 2014Lockhart 2013), olive leaves and fruits (Blazakis et al 2017), and legume leaves (Liao et al 2017), using geometric estimations allowed comparing and classifying differences among organ shapes that are not perceptible using conventional descriptors, and improving then the accuracy of plant descriptions. In sweet potato, the results showed that morphometric parameters should be included in morphological characterizations, and its potential is promising in physiological and genetic association studies.…”
Section: Constraints Of Conventional Morphological Characterization Isupporting
confidence: 85%
“…The potential use of phenomics in fruit shape description in tomato and eggplant has also been demonstrated (Brewer et al 2006;Plazas et al 2014), and its subsequent use in plant breeding (Kaushik et al 2016). In accordance with our results, quantification of leaf shape in barley (Chitwood et al 2013(Chitwood et al , 2014Lockhart 2013), olive leaves and fruits (Blazakis et al 2017), and legume leaves (Liao et al 2017), using geometric estimations allowed comparing and classifying differences among organ shapes that are not perceptible using conventional descriptors, and improving then the accuracy of plant descriptions. In sweet potato, the results showed that morphometric parameters should be included in morphological characterizations, and its potential is promising in physiological and genetic association studies.…”
Section: Constraints Of Conventional Morphological Characterization Isupporting
confidence: 85%
“…Chlorophyll content (i.e., total chlorophyll content) was found to be higher in transgenics than in WT after stress ( Figure 11C ). Similarly, membrane stability, which is a measure of ion leakage from the tissue, was used to analyze the damage caused to the members due to HS ( Niu and Xiang, 2018 ). However, no significant difference was found in membrane stability between the WT and transgenic plants ( Figure 11B ).…”
Section: Resultsmentioning
confidence: 99%
“…Our method is also well-suited for studying organ shape development, specifically when landmarks are difficult to assign. It could, therefore, be used to improve quantification and biological meaningfulness of previous EFA-based studies that, for example, decomposed entire leaf shapes ( Liao et al, 2017 ), insect wings ( Yang et al, 2015 ), jaw shape and sizes ( Rose et al, 2015 ) and pinniped whisker morphologies ( Ginter et al, 2012 ). LOCO-EFA can even be employed at different levels within the same organism, for example to quantify leaf shape and serrations as well as root morphology ( Li et al, 2017 preprint ).…”
Section: Discussionmentioning
confidence: 99%